Additive manufacturing of microstructured reactors for organometallic catalytic reactions. Issue 4 (22nd November 2022) - Otaola, Franco; Mottelet, Stéphane; Guénin, Erwann; Luart, Denis; Leturia, Mikel
Abstract : A comprehensive methodology for the development of microstructured reactors is proposed, including model conception and fabrication, material characterization, surface activation and performance evaluation of an organometallic reaction. Abstract : The use of Additive Manufacturing for the fabrication of chemical reactors for flow chemistry is a promising field as it can lead to several improvements over more standard equipment. In this work, two different reactors were fabricated and compared: a Honeycomb monolith reactor with straight channels and a Periodic Open Cell Structure reactor. The Honeycomb monolith reactor was used as an example of a standard reactor (not necessarily additive manufactured) while the Periodic Open Cell Structure is a promising new type of reactor, which improves some key features, such as contact surface area and porosity. The two reactors were manufactured by Stereolithography technology with a high temperature resin and their internal surfaces were chemically activated by the grafting of palladium. For the surface activation, a two-step procedure was developed, firstly using NaOH and in a second step an aqueous solution of Na2 PdCl4 . After activation, a heterogeneous catalytic reaction was used to characterize the performance of the two fabricated reactors. The chosen reaction was the Suzuki–Miyaura reaction, which is commonly used in the pharmaceutical industry. The experimental results showed that, for equal contact surface area, the new designed reactor had better performance compared to the standard geometry.